منافقین کے ساتھ مخاصمات میں مذکور اسماء الحسنیٰ کے اسرار و حکم: Mysteries and wisdom of Asma al Hasna mentioned in conversations with Hypocrites - Shamim Akhtar; Dr. Ammara Rehman (Al-Amīr Research Journal for Islamic Studies, 2024)
Asma-ul-Husna refers to the names that Allah as specifically designated for Himself. In the Holy Quran Asma-ul-Husnaa is mentioned at many places. It has a special relationship with the context. Allah Almighty mentioned His special not only a commandments and matter but also in the chapter of faith. The commandments of all semitic religions have been distorted except Islam, in Madina there was a group of people whose leader was a Abdulla bin Ubayy they were hypocrites. They called themselves "Muslim" but in Quran, they were addressed as hypocrites because of their actions and deeds. With reference to the mystery and order of Asma-ul-Husna, it is concluded that the mention of the names of Allah mentioned in the verses of the Mukhasamat (مخاصمات).It refers to a specific direction in each place, including “Sovereignty”, “Power”, “Perfection”, “Divinity”, “Lordship”, “Forgiveness”, and “Oneness”, “All-Knowing”, “The Best Planner” and many wisdom of expressing other, in which there is warning and instruction to the addresses. Keyword: Colon, Mystery, Wisdom, Asma-ul-husna, Hypocrites, Semitic.